Evaluación de los posgrados de la Facultad de Odontología de la Universidad de Antioquia entre 1982 y 1995 (referente histórico)* - Ossa-de D., Nury; Gualdrón-M., Carmen Sofía (Revista Facultad de Odontología Universidad de Antioquia, 2017)
In the investigation " Evaluation of graduate studies of the Faculty of Dentistry of the University of Antioquia between 1982 and 1995", in relation to the historical development of its programs, it was determined that from the begining in the 60's until now, there has been a series of changes in the objectives of formation as well as the duration, and the programs administration. From the begining, the programs depended administratively to a department until 1990, year in which an administrative reform in the Faculty took place. These programs were left without a direct link according to organization chart existent. The objectives of the initial phase (in the 60's) was to form faculty members intensifying in a specific area during a period of time depending on the necessity of the student and the availability of the professors. During the second phase of the graduates studies which starts in 1972, the objectives were focused on forming specialists in Orthodontics, Prothesis, Oral Medicine, with emphasis in basic sciences, techniques and clinical practice, then they could dedicated to teaching. This program was suspended in 1977. In 1982 graduated studies was initiated with a new "integrated" model and its objectives was formed specialists with knowledge, comprehension, liabilities and attitudes to attend patients with experience in investigation and administration.